Influence of Risk Management on Supply Chain management Projects in kenya : A case of Deloitte Kenya - Ngaji, Omuombo Arthur; Achuora, John (International Journal of Supply Chain and Logistics, 2019)
Purpose: This study examined the Influence of Risk Management on Supply Chain Projects in Kenya. Risk Management is a critical issue in the industry. The study sought to assess Influence of Risk Management on Supply Chain Projects in Kenya Methodology:The study adopted a descriptive survey design. The target population of the study was all the completed (566) Supply Chain Projects in Deloitte within the 2013 to 2017 strategic year period. The study used self-structured questionnaires to collect primary data from respondents and the data collected was cleaned, pretested, validated, coded, summarized and analysed using statistical package of SPSS V23. The study findings were presented using bar charts and pie charts. Results:The study found that the project managers had conceptual skills, technical skills, cost management skills, which positively influence Risk Management of supply chain projects. In addition, the study established that technological literacy and awareness, projects tools and equipment, skilled manpower, manpower training capacity, technological innovation, analytical and computational capacity and project team’s knowledge on ICT influence Risk Management in supply chain projects. Further, the study found that schedule development, schedule crashing, schedule compression, sequence of activities and schedule fast tracking influence Risk Management in supply chain projects. Also, the study found that factors such as the GDP cost of relocation of public utilities, inflation rates, variation of cost of labor, equipment hire rates, government debt service ratio, competing demands for government funds and unemployment rates influence Risk Management in supply chain projects. Contribution to policy and practice:Based on the study findings, the study concludes that risk planning influences Supply Chain Projects.The study also recommends that the government of Kenya should revise the current monitory policy governing inflation rates and foreign exchange rates so as to ensure the stability of foreign exchange rates and reduction in inflation rate.
Keywords: Risk Planning; Risk Response; Risk monitoring; Risk Assessment